2017
DOI: 10.1093/cercor/bhx008
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Body Mass Index is Associated with Increased Integration and Reduced Cohesion of Sensory-Driven and Internally Guided Resting-State Functional Brain Networks

Abstract: Elevated body mass index (BMI) is associated with increased multi-morbidity and mortality. The investigation of the relationship between BMI and brain organization has the potential to provide new insights relevant to clinical and policy strategies for weight control. Here, we quantified the association between increasing BMI and the functional organization of resting-state brain networks in a sample of 496 healthy individuals that were studied as part of the Human Connectome Project. We demonstrated that high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
51
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 82 publications
7
51
0
Order By: Relevance
“…Our finding is in line with and extends a recent report in which lower DMN connectivity was associated with higher BMI in a young sample but no differences of DMN functional connectivity in siblings with differing obesity status were found, indicating the connectivity differences to be subsequent, not prior to the development of obesity [Doucet et al, 2017]. In addition, previous studies on cardiovascular risk factors in middle-aged samples have linked insulin resistance and type 2 diabetes to alterations in default mode connectivity [Buckner et al, 2008;Kenna et al, 2013;Musen et al, 2012].…”
Section: Functional Connectivity and Obesity In Agingsupporting
confidence: 93%
See 1 more Smart Citation
“…Our finding is in line with and extends a recent report in which lower DMN connectivity was associated with higher BMI in a young sample but no differences of DMN functional connectivity in siblings with differing obesity status were found, indicating the connectivity differences to be subsequent, not prior to the development of obesity [Doucet et al, 2017]. In addition, previous studies on cardiovascular risk factors in middle-aged samples have linked insulin resistance and type 2 diabetes to alterations in default mode connectivity [Buckner et al, 2008;Kenna et al, 2013;Musen et al, 2012].…”
Section: Functional Connectivity and Obesity In Agingsupporting
confidence: 93%
“…In a recent study with 496 participants, DMN cohesiveness has been shown to be reduced in young, obese compared with lean individuals, with highest effect size found for the posterior DMN component which is in line with our results. A siblings analysis suggested this to be a consequence rather than a driving factor of obesity [Doucet et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…The atlas by Gordon et al () (hereafter referred to as the Gordon‐Atlas) was chosen because it is used in the Adolescent Brain Cognitive Development Study (https://abcdstudy.org/) which aims to provide national normative standards for brain FC (Casey et al, ). We included the atlases by Doucet et al () and Doucet, Rasgon, McEwen, Micali, and Frangou () (hereafter referred to as Doucet2011‐Atlas and Doucet2018‐Atlas) that were constructed by our group using resting‐state fMRI data from two independent large samples of healthy participants (Doucet et al, ; Doucet, Rasgon, et al, ). Details of the size of the sample used in the construction of each atlas, the method of RSN extraction and the RSNs defined are provided in Table , Figure and Table S1, Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…We included the atlases by Doucet et al (2011) andDoucet, Rasgon, McEwen, Micali, and (hereafter referred to as Doucet2011-Atlas and Doucet2018-Atlas) that were constructed by our group using resting-state fMRI data from two independent large samples of healthy participants (Doucet et al, 2011;Doucet, Rasgon, et al, 2018). Details of the size of the sample used in the construction of each atlas, the method of RSN extraction and the RSNs defined are provided in Table 1, Figure 1 and Table S1, Supporting Information.…”
Section: Selection Of Brain Functional Atlasesmentioning
confidence: 99%
“…Generally similar abnormalities in brain structure and neuronal network connectivity occur in individuals with type 2 diabetes (Macpherson et al, 2017). Even among individuals who are not obese, higher body mass index is associated with perturbed resting state connectivity in the DMN and sensory-motor networks (Beyer et al, 2017; Doucet et al, 2018). In addition, body mass index is inversely associated with glucose utilization in the prefrontal cortex, a brain region that plays critical roles in executive function, attention, memory, and insight (Volkow et al, 2009).…”
Section: Metabolic Factors Can Accelerate or Decelerate Brain Agingmentioning
confidence: 99%